Comparison of thermal and radar active layer measurement techniques in the Leaf Bay area, Nouveau-Québec - Pilon, Jean; Annan, A.; Davis, J.; Gray, James (Géographie physique et Quaternaire)

(untitled) (Les Presses de l’Université de Montréal, 1979)
Continuous profiles of the frost table for a series of traverses in unconsolidated sediments in the Leaf Bay area, Ungava, were obtained using an all terrain vehicle borne impulse radar system. The results correlate extremely well with data obtained by the insertion of rigid temperature probes at frequent intervals along the traverses. Each of the two systems has its own particular advantages and disadvantages. The radar profiling system provides more continuous information and can be carried out more rapidly than the system using the temperature probes. However, it requires some local ground control as regards soil moisture profiles and values for soil texture and soil temperature. A definite advantage of the rigid temperature probe is that it produces a temperature curve as a by-product and this can be used to assess the effect of different terrain factors on heat flow in the soil. It is, furthermore, a much cheaper and less bulky apparatus than the radar equipment, requiring no auxiliary logistical support for field use. Neither method can be applied universally for thaw zone and active layer determination. The trials in the tidal flats were a failure, the earth materials being too stony for the temperature probe and the salt water in the soil not permitting proper signal propagation for the radar. Neither method is suitable for penetrating bedrock and, in such a case, reliance has to be placed on temperature measurements in drillholes.